The impact of living space on dairy cow production, reproduction and welfare - Thompson, Jake S (2021)
The majority of dairy cows worldwide are housed for several months of the year, yet there is limited literature available on how the housed environment impacts on their productivity, health and wellbeing. The extent to which specific housing conditions affect individuals or herds of cows or how to improve housing to optimise productivity, health and welfare is unclear. Furthermore, the terminology used for housing requirements is often poorly defined or lacks a standard definition.